PERAN POKDARWIS DEWA BEJO DALAM PEMBERDAYAAN MASYARAKAT DESA WISATA BEJIHARJO - Fiki Andriyanto; Anisa Wihayati (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2021)
Indonesia is a developing country that has a lot of potential resources, therefore the government is always doing development to optimize this potential. In the 2018 Ministry of Tourism performance report, the tourism industry is one of the focuses of the 5-year development program because it plays a strategic role in national development. Pokdarwis Dewa Bejo, who understands the potential of his village, seeks to help the government's efforts by carrying out several community empowerment roles in Bejiharjo Village to successfully turn the village into a tourist village. This paper describes the role played by Pokdarwis Dewa Bejo in community empowerment in Bejiharjo Village. The research method used is qualitative with literature study. From this study, it is known that several roles performed by Pokdarwis Dewa Bejo include planning, accelerating, educator, mediator, and advocating well. This role makes community empowerment activities in Bejiharjo Village able to increase people's income. Keywords: The Role of Community Empowerment, Pokdarwis Dewa Bejo, Bejiharjo Tourism Village.